A quantitative evaluation of fluid leakage around a polyvinyl chloride tapered endotracheal tube cuff using an in-vitro model - Shiotsuka, J (EDIMES Edizioni Internazionali Srl, 2012)
INTRODUCTION: This study was designed to quantitatively evaluate the sealing effect of a polyvinyl chloride tapered endotracheal tube cuff and to compare the tapered cuff with cylindrical endotracheal tube cuffs using an in vitro viscous fluid model. METHODS: Five types of 8.0 mm inner diameter endotracheal tubes (TaperGuard, PortexSacett, PortexSoftseal, Sheridan HVT, Sheridan CF) were fixed in vertically placed 20mm internal diameter acrylic tubes. The cuffs were inflated to 25 mmHg pressure and water was added to the top of the cuff. The amount of water leaking around the cuff at five minutes was measured. Afterwards a viscous fluid was poured above the cuff and the amount of fluid passing around the cuff at five minutes and four hours was measured. Each determination was repeated five times and the data analyzed. RESULTS: The median (range) amount (ml) of dyed water passing around the cuff at 5 minutes was TaperGuard tube 0 (0-0.2), PortexSacett 81.1 (44.6-107.9), PortexSoftseal 95.4 (91.4-113.7), Sheridan HVT 46.5 (32.7-74.6) and Sheridan CF 52.6 (31.9-62.2), suggesting that TaperGuard significantly (P<0.05) reduced fluid leakage. The viscous fluid leakage at 5 minutes was not significantly different among the groups while the amount of leaked viscous fluid at 4 hours was 0.2 (0-1.1) for the TaperGuard, 57.6 (11.9-117.4) for the PortexSacett, 23.2 (13.8-33.0) for the PortexSoftseal, 5.5 (2.7-15.4) for the Sheridan HVT and 5.6 (1.8-7.9) for the Sheridan CF. CONCLUSION: An endotracheal tube with a tapered polyvinyl chloride cuff had significantly less fluid leakage compared to four tubes with cylindrical cuffs.